2019
DOI: 10.3390/polym11101725
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Stiffness of Coupled and Uncoupled Recycled Cotton Fibers Reinforced Polypropylene Composites

Abstract: The stiffness of a composite material is mainly affected by the nature of its phases and its contents, the dispersion of the reinforcement, as well as the morphology and mean orientation of such reinforcement. In this paper, recovered dyed cotton fibers from textile industry were used as reinforcement for a polypropylene matrix. The specific dye seems to decrease the hydrophilicity of the fibers and to increase its chemical compatibility with the matrix. The results showed a linear evolution of the Young’s mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The values obtained for the modulus efficiency factor are in the range between 0.47 and 0.49. These values can be considered reasonable as they are in line with the literature [ 61 , 62 ]. However, the values show how only around 50% of the stiffening capabilities of the reinforcement is exploited.…”
Section: Resultssupporting
confidence: 85%
“…The values obtained for the modulus efficiency factor are in the range between 0.47 and 0.49. These values can be considered reasonable as they are in line with the literature [ 61 , 62 ]. However, the values show how only around 50% of the stiffening capabilities of the reinforcement is exploited.…”
Section: Resultssupporting
confidence: 85%
“…The modulus efficiency factor was found inside the usual range for short, semi-aligned natural fibers, which is 0.4–0.56 [ 67 ]. Thereby, the value indicated that the composites took advantage of the stiffening capability of natural fibers, though with room for improvement.…”
Section: Resultsmentioning
confidence: 99%
“…One of the simplest methods used to express the contribution of the phases to the material's strength is by using the modified Rule of Mixtures (mRoM) [63,64]. The model was initially developed to be applied to tensile properties, though, it can also be extended to flexural ones.…”
Section: Intrinsic Flexural Strength Propertiesmentioning
confidence: 99%